EXPLORING CULTURAL DIMENSION AND ITS IMPACT ON TRANSFORMATIONAL LEADERSHIP STYLE IN INDONESIA (A STUDY AT STATE ISLAMIC UNIVERSITY OF MAULANA MALIK IBRAHIM-MALANG) - Mohamed, Assalhen Abdualsslam; Rofiaty, - (Accounting Department,, 2016)
This study examines the cultural dimensions practiced by leaders and the impact of the cultural dimensions on leadership styles of leaders in State Islamic University of Maulana Malik Ibrahim. The variables used in this study are five cultural dimensions and transformational leadership style. This study applies quantitative method to reveal the effect of independent on dependent variables.This study used employees’ perspective of their leader characters to reveal the cultural dimensions and its effect on transformational leadership style. Data collection method used in this research was probability sampling method with the sample of 90 employees at State Islamic University of Maulana Malik Ibrahim. The hypotheses were tested using logistic regression analysis. The results showed that the leaders at State Islamic University of Maulana Malik Ibrahim practiced big power distance which causes gaps among the leaders and employees. They also tend to be individualism-based in managing the organization. With the power focus, they possess masculine culture in which more logical reasoning is highlighted. Although they can accept uncertainty of the results, the leaders still focus on the future benefits of every decision they make. Moreover, the independent variables power distance, uncertainty avoidance, and terms of orientation significantly influence transformational leadership style practiced at the university. However, individual/collectivism and masculinity/femininity factors do not have any influence on the implementation of transformational leadership style in this university.